Effects of a digital tool implementing the German S3 clinical practice guideline for multimorbidity in primary care (gp-multitool.de): study protocol for a cluster-randomised controlled trial - Julia Nothacker; Martin Scherer; Antonia Zapf; Ingmar Schäfer; Dagmar Lühmann; Susanne Lezius; Agata Menzel; Linda Krause; Valentina Paucke (BMJ Open)
Introduction Multimorbidity is prevalent and associated with complex treatment requirements. In order to assist general practitioners (GPs) addressing these requirements, the web application gp-multitool.de has been designed, which facilitates implementation of the German clinical practice guideline for multimorbidity. We will conduct a cluster-randomised clinical trial evaluating an intervention based on this tool. This protocol summarises methods and discusses ethics and dissemination of this study.Methods and analysis Participating patients are recruited by cooperating GP practices. Inclusion criteria are an age of 65 years or older, enrolment in any disease management programme and multimorbidity operationalised by two additional chronic conditions. To avoid postrandomisation selection bias, practices are randomised as clusters after baseline assessment of all participating patients from the respective practice. In our intervention, patients receive access to different assessments including patient preferences by email, fill out the electronic assessment forms on any device with access to the internet, receive a medication review and discuss the assessment results with their GPs. GPs in the control group do not have access to the digital tool and provide care as usual. The primary outcome is staying at least once for at least one night in hospital during the 12-month observation period. Secondary outcomes are contacts with GPs and outpatient specialists, self-reported health, health-related quality of life, patient satisfaction and GP-reported and patient-reported quality of care. A sample size of 660 patients from 66 GP practices is needed. Data are analysed by mixed effects regression models.Ethics and dissemination Ethics approval was obtained by the ethics committee of the Medical Association of Hamburg (2022–1 00 786-BO-ff). Study results will be presented on scientific conferences and published in journal articles. In addition, healthcare professionals, patient representatives and the interested public will be informed about study results at a symposium.Trial registration number The study was registered in clinicaltrials.gov (NCT06831994).